THE POTENCY OF MESOPOROUS CARBON (CMK-1) AS ADSORBENT OF DYES - , Paulina Taba ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
Dyes are group of substances used widely in industries. These substances can introduce problems in an aqueous environment. Adsorption is an effective method for lowering the concentration of such materials in the environment. This work deals with dye adsorption using mesoporous carbon (CMK-1) as the adsorbent. For comparison, activated carbon (Norit SX22) was also used as adsorbent. CMK-1 was synthesized using mesoporous silica (MCM-48) as a template and sucrose as a carbon source. Sulphuric acid was utilized as a catalyst in carbonization process. After carbonization, the silica wall was dissolved by sodium hydroxide solution in ethanol-water of 1:1. To synthesize MCM-48, sodium silicate was used as a silica source and a mixture of cationic surfactant (cetyltrimethylammonium bromide, CTAB) and neutral surfactant (Triton X-100) as template. Adsorbates used were reactive (reactive red-1, RR1), basic (Rhodamine B, RhB), and acid (Patent Blue V, PBV) dyes. The optimum contact time of dyes with CMK-1 was 120 min. The adsorption of the dyes in CMK-1 and activated carbon can be fitted to both the Langmuir and Freundlich models, although with the possible exception of RR1 in activated carbon, statistically better fits are obtained with the Langmuir model. The adsorption of the dyes using CMK-1 was considerable higher than that using Norit SX2. The amount of dyes adsorbed by CMK-1 was in the order of RR1 &gt